Strength Characteristics of Polypropylene Fiber-Modified Rubber Foamed Concrete - Yanzi Wang; Mingzhen Tian; Sindambiwe Theogene; Jianzhu Wang; Bin Lv; Xinyi Zhang; Haixia Gong; Hongbo Zhang; Yazhen Liu (Buildings)
To address the challenge of balancing static and dynamic strength in the engineering application of foam concrete, this study proposes a strategy to improve the static and dynamic mechanical properties of foam concrete by synergistically adding rubber particles and polypropylene fibers, and systematically analyzes the effects of rubber content, rubber particle size, and fiber content on the material’s compressive strength, flexural strength, and impact toughness. The results show that rubber enhances the dynamic strength of foam concrete through high elastic deformation, with a maximum increase of up to 200%. However, due to the obstruction of hydration reaction, the increase in rubber content reduces the compressive and flexural strength of foam concrete. Meanwhile, the influence of rubber particle size on static strength follows a parabolic trend, with the optimal overall performance achieved at a particle size of 20-mesh, resulting in an approximately 50% enhancement in compressive strength. The addition of fibers to form a three-dimensional mesh structure connecting the cement matrix and rubber particles to inhibit the expansion of cracks can effectively alleviate the deterioration of the static strength of foam concrete caused by rubber particles. The optimal fiber content is 0.2%. In addition, the fiber can also improve the dynamic strength of foam concrete. In addition, the mechanism behind the synergistic improvement of static and dynamic strength by rubber and fiber was summarized. Finally, the optimized proportion and the prediction formulas of static and dynamic strength are established for the above three strength indexes, and the accuracy of the prediction formulas can reach more than 90%.